METHOD OF OPERATIONAL QUALITY CONTROL OF MEAT RAW MATERIALS AND MEAT PRODUCTS - Приліпко, Тетяна; Коваль, Т.В. (Modern engineering and innovative technologies, 2023)
Taking into account the prevalence of methods and means of measuring electrical quantities in metrological practice, it is advisable to carry out their analysis regarding the possibility of application for operational identification of types of meat. The